ANALYSIS OF THE MASTERY OF CHINESE LANGUAGE PUNCTUATION AMONG STUDENTS OF THE MANDARIN LANGUAGE EDUCATION PROGRAM, 2020 BATCH, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS TANJUNGPURA - Julita Julita; Ina Ina; Suhardi Suhardi (Bambuti, 2023)
Abstract Punctuation is an essential tool to aid written expression. The correct use of punctuation ensures that the reader accurately understands the text. However, in the process of writing, students majoring in Chinese language education at Universitas Tanjungpura encountered many difficulties, such as many errors in the writing form, format, and use of functions. To understand the mastery, difficulties, and reasons for the 2020 students majoring in Chinese Language Education at the Faculty of Teacher Education of Universitas Tanjungpura, the author used testing and questionnaire survey methods to conduct research. The test results showed that the student's mastery of Chinese punctuation marks was 54,85%, the error rate in writing form accounted for 69,55%, the error rate in format accounted for 54,80%, and the error rate in usage accounted for 40,20%. Although they have seen or used it in learning, that does not mean they can master it well. Through the analysis of error types and questionnaires, the author found three main reasons for students' errors in using Chinese punctuation: students, teachers, and other objective aspects. Abstrak Tanda baca adalah alat bantu penting dalam mengekspresikan bahasa tulisan. Penggunaan tanda baca yang benar dapat membuat pembaca memahami maksud dari isi teks. Namun pada saat mengarang, mahasiswa prodi pendidikan bahasa Mandarin FKIP UNTAN masih sering melakukan kesalahan, seperti penulisan, format penulisan, serta cara penggunaan tanda baca. Untuk mengetahui penguasaan, kesulitan dan alasan kesulitan mahasiswa angkatan 2020 Program Studi Pendidikan Bahasa Mandarin FKIP UNTAN terhadap tanda baca bahasa Mandarin, penulis menggunakan metode tes dan metode kuesioner. Hasil tes menunjukkan bahwa kondisi penguasaan mahasiswa terhadap tanda baca bahasa Mandarin adalah sebesar 54,85%, kesalahan dalam segi penulisan tanda baca mencapai 69,55%, segi kesalahan format penulisan tanda baca mencapai 54,80%, dan dalam segi kesalahan penggunaan tanda baca mencapai 40,20%. Meskipun dalam proses pembelajaran mereka sudah pernah melihat ataupun pernah menggunakannya, bukan berarti mereka dapat menguasainya dengan baik. Melalui analisis kesalahan penggunaan dan hasil kuesioner, penulis menyadari bahwa terdapat tiga aspek utama penyebab kesalahan mahasiswa dalam penggunaan tanda baca bahasa Mandarin, yaitu disebabkan oleh mahasiswa itu sendiri, guru, dan aspek objektif lainnya.